#### Answer

P(B)=.1

#### Work Step by Step

Step 1 P(AUB)=P(A)+P(B)-P(AnB)
Step 2. .4=.3 + P(B)-0
Step 3 Solve

Published by
Brooks Cole

ISBN 10:
1133607705

ISBN 13:
978-1-13360-770-0

P(B)=.1

Step 1 P(AUB)=P(A)+P(B)-P(AnB)
Step 2. .4=.3 + P(B)-0
Step 3 Solve

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.